2012
DOI: 10.1080/16823206.2012.745756
|View full text |Cite|
|
Sign up to set email alerts
|

Viewing teacher transformation through the lens of cultural-historical activity theory (CHAT)

Abstract: Technology-Enhanced Formative Assessment (TEFA) is an innovative pedagogy for science and mathematics instruction. The 'Teacher Learning of TEFA' research project studies teacher change as in-service secondary science and mathematics teachers learn TEFA in the context of a multi-year professional development programme. Applying cultural-historical activity theory (CHAT) to the linked activity systems of professional development and teachers' classroom practice leads to a model of teacher learning and pedagogic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Context of the studies Table 1 shows that the reviewed studies used CHAT for varying purposes. For example, Beatty and Feldman (2012) viewed teacher transformation through the lens of CHAT and thus studied teacher change and pedagogical change as in-service secondary science and mathematics teachers learned Technology-Enhanced Formative Assessment (TEFA) in the context of a multi-year professional development program, termed Teacher Learning of TEFA (TLT). Their intention was to help the teachers to learn to use TLT successfully in their classes.…”
Section: Analysis Of Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Context of the studies Table 1 shows that the reviewed studies used CHAT for varying purposes. For example, Beatty and Feldman (2012) viewed teacher transformation through the lens of CHAT and thus studied teacher change and pedagogical change as in-service secondary science and mathematics teachers learned Technology-Enhanced Formative Assessment (TEFA) in the context of a multi-year professional development program, termed Teacher Learning of TEFA (TLT). Their intention was to help the teachers to learn to use TLT successfully in their classes.…”
Section: Analysis Of Literaturementioning
confidence: 99%
“…Mostly, they either made mention of general terms of analysis which were even not well elaborated or analyzed a part of them, despite variations in collection. For instance, Beatty and Feldman (2012) collected data from four sites in a span of one baseline semester and 2 to 3 years of professional development. Having collected data on the participants' backgrounds, outlooks, experiences, and classroom practice of TEFA through multiple instruments and methods, they left the instruments and methods unidentified.…”
Section: Description Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, it allows for analysis of the supportive and contradictory relationships between different components of the activity system, especially identification of inner contradictions within the activity system (Engeström, 1987(Engeström, , 2001Yamagata-Lynch & Haudenschild, 2009). Research has found that contradictions play a central role in shaping how the subject of activity functions and develops within the activity system; they can cause tensions and inhibit development, but also have the capacity to motivate change and development through innovations in collective contradiction resolution (e.g., Ahn, 2011;Beatty & Feldman, 2012;J. Cross, 2011;Dang, 2013;Yamagata-Lynch & Haudenschild, 2009).…”
Section: Theoretical Frameworkmentioning
confidence: 99%